2019
DOI: 10.1002/anie.201812174
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Boron Coordination: B←N Bond Supports a [2+2] Photodimerization in the Solid State and Generation of a Diboron Bis‐Tweezer for Benzene/Thiophene Separation

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Interestingly, guest recognition may occur in both cavities within this framework resembling a double‐tweezer host, and structural syn / anti ‐isomerism is feasible, which might enable the encapsulation of even two different guest molecules (Scheme c). Moreover, these double‐tweezer hosts were shown to perform “catch‐release” cycles of polycyclic aromatic hydrocarbons (PAHs) such as pyrene from solution mixtures, to accomplish the separation of o ‐xylene from an equimolar mixture of o ‐, m ‐ and p ‐xylene isomers by enrichment through fractional crystallization, and to behave as molecular scavengers for the selective removal of sulfur‐based aromatics such as thiophene …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, guest recognition may occur in both cavities within this framework resembling a double‐tweezer host, and structural syn / anti ‐isomerism is feasible, which might enable the encapsulation of even two different guest molecules (Scheme c). Moreover, these double‐tweezer hosts were shown to perform “catch‐release” cycles of polycyclic aromatic hydrocarbons (PAHs) such as pyrene from solution mixtures, to accomplish the separation of o ‐xylene from an equimolar mixture of o ‐, m ‐ and p ‐xylene isomers by enrichment through fractional crystallization, and to behave as molecular scavengers for the selective removal of sulfur‐based aromatics such as thiophene …”
Section: Introductionmentioning
confidence: 99%
“…10 g , h Recently, the B←N dative bond has appeared to serve as a good alternative to traditional non-covalent and metal–coordinate bonds, to build supramolecular network/host–guest-based crystalline assemblies, for various applications. 11–20 In general, the donation of electrons from the N-donor ligand to the electron-deficient boron atom (empty p-orbital) stabilizes such type of bonding. It has also been observed that the electronic properties of the interacting partner strongly influence the strength of the B←N dative bond.…”
mentioning
confidence: 99%
“…Stacking of the C=C bonds in the dimer fulfilled the geometric criteria of Schmidt for a [2+2]-photocycloaddition affording rctt-1,3-bis(4′-pyridyl)-2,4-bis(phenyl)cyclobutane (ppcb) upon UV irradiation (Scheme 6). 32 Crystallization of the components afforded a T-shaped boronic ester adduct of composition (be)•(4-sbz) wherein 4-sbz was positioned orthogonally to be. Self-assembly of two monoboron adducts generated a discrete dimer with a head-to-tail geometry (ht) sustained by ••• and C-H••• contacts (Figure 6a,b).…”
Section: Boronic Esters As Templates For [2+2]-photocycloadditions In the Solid Statementioning
confidence: 99%